The image, culture and politics in the extraordinary electoral process in Arequipa Peru - Cusihuamán Sisa, Gregorio Nicolás (2020)
The investigation examines the culture, politics, and image of political parties in the extraordinary electoral process for Congress, held in January of this year in Peru; from a political communication perspective. The objective is to demonstrate the level of articulation of the factors that build a democratic society in an electoral process, the relations between culture and politics have a long history, however, the levels of articulation in political language have their expression in the image they project to society, that being the fundamental reason for the article. The applied descriptive methodology combines techniques for analyzing image observation formats with interviews, generating qualitative and quantitative results. The conclusions show a disarticulation of concomitant elements in the consolidation of the democratic political order, the perception of a mono-culture aimed at solving the situation without prospective, the de-ideologization of political organizations and the predominance of the image of the "leader" over that of the "leader". Party is a constant that degenerates the institutional strengthening of political organizations.